Fiqh Al-Ḥaḍarah from a Geopolitical Perspective: The Idea of NU's Peace Diplomacy Through the Recontextualization of Political Jurisprudence - Rois, Choirur; Masrury, Farhan; Zikri, Arfad (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2023)
The conception of the jurisprudence of civilization (fiqh al-Ḥaḍarah) as an idea of peace diplomacy offered by Nahdlatul Ulama (NU) is the main starting point of this study. This idea presents religious thoughts as a solution to various unsolved conflicts. For example, the Middle East issue gave rise to stereotypes and negative images of Islam as the basis for conflict under the pretext of jihad as a movement idea. Based on the results of the International Conference on the Jurisprudence of Civilization I, in Nahdlatul Ulama's view, the recontextualization of political jurisprudence from a geopolitical perspective, on the one hand, is critical as a basis for understanding carrying out Islamic teachings in the political sector of state administration. On the other hand, it is also an effort to create sustainable peace. The question here is how can the recontextualization of political jurisprudence in the view of Nahdlatul Ulama be used as an idea for world peace diplomacy when viewed from a geopolitical perspective. This paper uses a descriptive qualitative method with data collection using desk research and an annotated bibliography. The approaches used include textual-contextual, sociological approach to Islamic law, and the theory of critical discourse analysis. This research shows that, based on NU's view from a geopolitical perspective, fiqh al-Ḥaḍarah can be used as a term to re-contextualize political jurisprudence discourse in an ideal direction. It is according to the needs and demands of the era. It presents islamic jurisprudence thinking as a solution to welcoming a better civilization in the future, either as a diplomatic idea or as an idea of sustainable peace. Abstrak: Tulisan ini berangkat dari konsepsi fikih peradaban (fiqh al-haḍarah) sebagai gagasan diplomasi perdamaian yang ditawarkan oleh Nahdlatul Ulama (NU) kepada dunia untuk menghadirkan gagasan agama sebagai solusi atas berbagai konflik yang tak kunjung selesai sampai saat ini. Seperti halnya studi kasus di Timur Tengah yang memunculkan stereotipe dan citra negatif atas Islam sebagai dasar konflik dengan dalih jihad sebagai ide gerakan. Dalam pandangan Nahdlatul Ulama berdasarkan hasil Muktamar Internasional Fikih Peradaban I, rekontekstualisasi fiqh siya>sah dalam perspektif geopolitik menjadi sangat penting untuk dilakukan sebagai dasar pemahaman dalam menjalankan ajaran Islam di sektor politik ketatanegaraan serta sebagai upaya dalam mewujudkan perdamaian yang berkelanjutan. Lantas bagaimana rekontekstualisasi fiqh siya>sah dalam pandangan Nahdlatul Ulama bisa dijadikan gagasan diplomasi perdamaian dunia jika dilihat dari perspektif geopolitik? Tulisan ini disusun menggunakan metode kualitatif deskriptif dengan pengumpulan data menggunakan metode desk research dan annotated bibliography. Pendekatan yang digunakan diantaranya, tekstual-kontekstual, pendekatan sosiologi hukum Islam dan teori analisis wacana kritis (critical discourse analysis). Hasil dalam tulisan ini menunjukkan bahwa, berdasarkan pandangan NU dalam perspektif geopolitik fiqh al-haḍarah dapat dijadikan sebagai istilah untuk dapat merekontekstualisasikan diskursus fiqh siya>sah ke arah yang lebih ideal sesuai dengan kebutuhan dan tuntutan zamannya serta menghadirkan pemikiran fikih sebagai solusi dalam menyongsong peradaban yang lebih baik di masa depan. Baik sebagai suatu gagasan diplomasi ataupun sebagai ide gagasan perdamaian yang berkelanjutan.